Analisis Pengaruh Kesenjangan Generasi terhadap Kualitas Kerja Karyawan di dalam Perusahaan - Saepulloh Hidayat; Fauzan Riezky Hutama; Muhamad Ardi Nupi Hasyim (Jurnal Riset Manajemen Indonesia, 2023)
The title of this study is an analysis of marketing strategies to increase sales at PT Nusantara Turbine and Propulsion in Bandung. This study aims to find out how the marketing strategy implemented by MSME businesses to increase sales. Methods of data analysis in this study researchers used descriptive data method with a qualitative approach. The collection of data in this study came from primary sources that came directly from employees, namely by using a questionnaire distributed to employees of PT Nusantara Turbin and Propulsi.